A SYSTEM FOR RECOGNITION OF DESTINATION ADDRESS IN POSTAL DOCUMENTS OF INDIA - Roy, Ramit Kumar; Pal, Umapada; Roy, Kaushik; Kimura, Fumitaka (Malaysian Journal of Computer Science, 2020)
Recognition of destination address is compulsory for automation of the postal system in India. Our observation found that such recognition becomes a very challenging task due to inter-mixing of three languages (Hindi, English and the official language of the particular state in which the postal document is supposed to reach).In this paper, our attempt towards development of a dynamic programming based system for city-name and pin code recognition of destination address in postal documents of India not only managed to address the difficulties related to identification of the scripts but also managed to get rid of those problems which is generated due to character touching in postal documents. For city-name recognition, lexicon information is used. However, no lexicon information is used for pin code recognition since an Indian pin code contains only 6 digits. We obtained 99.55% reliability from tri-lingual city-name recognition system where error rates are 0.20% and rejection rates are 28.11%. From our experiment on recognition of handwritten pin codes, 99.01% reliability rate, 0.83% error rate and15.27% rejection rate are obtained. Furthermore, to enhance the city-name results by distributing the lexicon size district-wise, we conducted an experiment and presented the results.